Where Were the “Goose” and the “Gorodets” of Shakh-Ali bin Sheikh Auliyar’s Charter of 1543? - A.V. Deduk (Золотоордынское обозрение)
Objective: Based on the methods of historical geography, the author identifies the location of the “Goose” and “Gorodets” mentioned in the act of 1543. Research materials: Various written sources were used in this study, including primarily act materials, chronicle accounts and land records (“pistsovye knigi”). Results and novelty of the research: The article deals with the question of location of the Goose and Gorodets volosts (counties). They are mentioned in the charter of 1543 issued by Shakh-Ali to the Trinity monastery of St. Sergius. The author doubts the possibility of finding them in the Kashira district. This localization was held by M.G. Khudyakov, A.V. Belyakov and B.R. Rakhimzyanov. The author concludes on the location of the “Goose” volost (county) in the lands of Vladimir district. Gorodets fits with Gorodets Meshchersky (Kasimov). Much attention is given to the political and administrative affiliation of the Goose district (“volost”). In my opinion, the presented information may be interesting for the study of the historical geography of the Kasim “khanate”. The research presented in the article allow us to establish that the territory of Kasimov and Gorodets was considered in 1543 as the “votchina” (derived from the word “Father”) of the Grand Duke. This article can be very useful for the historians who deal with boundaries of the counties of the 16th century.